„Feature” w radiu – wymykanie się wyznacznikom gatunku. Uwagi genologiczne po festiwalu Prix Europa w latach 2012 i 2013 - Bachura-Wojtasik, Joanna; Klimczak, Kinga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The goal of the article is to answer the question: what do radio broadcasters in the west understand to be a ‘feature’? A lack of clarity in terminology in this respect was especially visible during the Prix Europa 2012 and 2013 festivals. The article begins with an outline of the term ‘feature’, followed by discussion of relevant festival categories, and ending with a presentation of several selected audio examples that indicate both the characteristics of the genre and cases where in spite of divergences from these qualities, the term ‘feature’ continues to function.